Neural efficiency in EFL learning and positive psychology - Liwei Hsu (PLoS ONE, 2025)
This study aims to investigate how teachers’ positive feedback influences learners’ positive psychology in English as a Foreign Language (EFL) instruction and to examine how positive psychology enhances learning outcomes through the neural efficiency hypothesis. The study employed three neuroscientific and behavioral experiments to address these questions. Study 1, with 78 college-level EFL learners, examined the effect of teachers’ positive feedback on learners’ positive psychology and found a significant positive impact. Study 2, conducted with 102 EFL learners, tested the neural efficiency hypothesis and revealed that higher positive psychology improved neural efficiency, with positive feedback moderating this effect. Study 3, involving 54 EFL learners, explored the relationship between neural efficiency and learning outcomes, confirming that enhanced neural efficiency leads to better learning performance. Beyond education, the results underscore the broader relevance of positive psychology and neural efficiency in other domains, such as workplace performance, skill acquisition, and personal development, where maintaining cognitive efficiency and well-being is crucial. These findings highlight the importance of positive feedback in fostering positive psychology, improving neural efficiency, and enhancing learning outcomes. The study offers theoretical contributions and practical recommendations for EFL educators to leverage positive feedback and promote effective learning.